FUNCTIONAL RESPONSE OF Diplonychus indicus VENK. & RAO (HEMIPTERA: BELOSTOMATIDAE) AGAINST Aedes aegypti LINNAEUS AND Aedes albopictus SKUSE (DIPTERA: CULICIDAE) - MARIN, GRACE; PEARLIN, ASKILLA; BLESSY, PAULRAJ; GINCY, DEVASANTHAKUMAR; ARIVOLI, SUBRAMANIAN; TENNYSON, SAMUEL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The predatory efficiency of the hemipteran water bug Diplonychus indicus was evaluated for its functional response against its prey Aedes aegypti and Aedes albopictus larvae for 72 hours with varied prey densities. The number of prey killed increased with increasing prey density from 1 prey per single predator to 32 prey per single predator. The attack rate increased with the increase of prey density level, and was at its peak at 16 prey density (22.30) and lowest at 4 prey density (3.77) for Aedes aegypti; and for Aedes albopictus it was at one prey density (7.70) and the lowest at the maximum prey density level (3.44). Diplonychus indicus fed on Aedes aegypti and Aedes albopictus larvae took 0.0193 days (27.79 minutes) and 0.0108 days (15.55 minutes) handling time respectively. The predator killed maximum number of 140.22 Aedes aegypti and 151.07 Aedes albopictus larvae after 72 hours, when the prey density level was 32. Regression analysis of prey density against number of prey attacked for 72 hours observation yielded a significantly positive slope for both Aedes aegypti and Aedes albopictus. The predation experiment revealed that the functional response analysis of Diplonychus indicus exhibited a Type II functional response. Several factors affect the functional response of a predator’s search mode, especially strike and foraging success, which are complex and can be understood only by looking at each component separately.